The interconnectedness of stock prices, money, and credit across time and frequency from 1970 to 2016 - Ryczkowski, Maciej; Zinecker, Marek (Technological and Economic Development of Economy, 2022)
This article applies continuous wavelet and maximal overlap discrete wavelet transforms to study the co-movements and the direction of causality between money (M3 and M2), bank credit, credit from all sectors vs. stock price dynamics across time and frequency for 12 developed countries. The time-varying linkages were significant typically for credit rather than money developments. Particularly, these linkages appeared during phases of house and stock price boom and bust at a business cycle frequency. The discovered lead-lag patterns give relatively much time for monetary policy authorities to support their financial stability objectives by imposing restrictions on credit. Closing the channel through which credit and stock prices interact may counteract the rising financial imbalances. This finding holds also for the euro area where the monetary pillar is based on broad money. The new application of wavelets allowed discovering the varying linkages that were not necessarily evident in the standard methods of analysing data.First published online 08 July 2022